Some Hardy's inequalities on conformable fractional calculus - AlNemer Ghada; Saker Samir H.; Ashry Gehad M.; Zakarya Mohammed; Rezk Haytham M.; Kenawy Mohammed R. (Demonstratio Mathematica, 2024)
In this article, we will demonstrate some Hardy’s inequalities by utilizing Hölder inequality, integration by parts, and chain rule of the conformable fractional calculus. When α=1α =1, we can obtain some of classical Copson’s and Hardy’s inequalities. In the end, we will obtain an application of Hardy’s inequality utilizing the conformable fractional calculus.